1999
DOI: 10.1136/adc.81.5.417
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic markers of infection: comparison of procalcitonin with C reactive protein and leucocyte count

Abstract: Background-Procalcitonin has been advocated as a marker of bacterial infection.Objective-To evaluate diagnostic markers of infection in critically ill children, comparing procalcitonin with C reactive protein and leucocyte count in a paediatric intensive care unit (PICU). Methods-Procalcitonin, C reactive protein, and leucocyte count were measured in 175 children, median age 16 months, on admission to the PICU. Patients were classified as: non-infected controls (43); viral infection (14); localised bacterial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
123
1
15

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(152 citation statements)
references
References 29 publications
13
123
1
15
Order By: Relevance
“…In our previous study, serum PCT levels seemed to be superior to serum CRP levels in terms of early diagnosis of neonatal sepsis, in detecting the severity of the illness, and in evaluation of the response to antibiotic treatment. 25 This was similar to findings of some, 26,27 but not all 28,29 studies. Therefore, in some studies multiple comparisons were made between CRP, PCT and other cytokines such as IL-6, IL-8 and tumor necrosis factor-a.…”
Section: Saa Crp and Pctsupporting
confidence: 81%
“…In our previous study, serum PCT levels seemed to be superior to serum CRP levels in terms of early diagnosis of neonatal sepsis, in detecting the severity of the illness, and in evaluation of the response to antibiotic treatment. 25 This was similar to findings of some, 26,27 but not all 28,29 studies. Therefore, in some studies multiple comparisons were made between CRP, PCT and other cytokines such as IL-6, IL-8 and tumor necrosis factor-a.…”
Section: Saa Crp and Pctsupporting
confidence: 81%
“…Procalcitonin is one of the applicable markers to detect bacterial infection in children and adults. 6 Plasma PCT level is comparable with specific response of bacterial infection, particularly for invasive or probably-invasive bacteria. High concentration of PCT indicates sepsis, severe sepsis or even septic shock condition.…”
Section: Introductionmentioning
confidence: 86%
“…A procalcitonin concentration of 2 ng/ mL might be useful in differentiating severe bacteri al di sease i n i nf ants and chi l dren. 6 Another study conducted in Department of Anesthesiology and Critical Care, and Department of Pharmacy, Military Hospital, Tunis University, Tunis to compare the accuracy of PCT to diagnose postoperative infection after cardiac surgery and compare it with those of C-reactive protein, white blood cell count, and interleukins 6 and 8 concluded that PCT is a valuable marker of bacterial infections after cardiac surgery. 8 This study was conducted to evaluate the sensitivity of PCT compared to leucocyte count in the diagnosis of bacterial infection after surgery in patients who underwent major surgery at Dr. Sardjito General Hospital, Yogyakarta.…”
Section: Introductionmentioning
confidence: 99%
“…A reliable marker of infection or a set of markers that can quickly and accurately diagnose these infections using small volumes of peripheral blood could lead to faster, more effective treatment. A variety of biomarkers have been studied that include hematologic parameters such as immature/total neutrophil ratio (Rodwell et al, 1988 andBerger et al, 1995), C-reactive protein (Berger et al, 1995;Ng et al, 1997;Wagle et al, 1994;and Hatherill et al, 1999), procalcitonin (Hatherill et al, 1999;Gendrel et al, 1996), TNF-α (Ng et al, 1997), IL-1β (Ng et al, 1997), soluble IL-1ra (Küster et al, 1998), IL-2 receptor (Jurges and Henderson, 1996), IL-6 (Ng et al, 1997 andKüster et al, 1998), IL-8 (Franz et al, 1999 andBerner et al, 2000), IL-10 (van der Poll et al, 1997) and markers of complement activation (Zilow et al, 1993). Each of these markers offers some utility to the clinician during acute care of the infant, but they have yet to become a routine test for care of acutely ill infants in most settings.…”
Section: Cell Markers Of Infectionmentioning
confidence: 99%